Aplicación informática para la Gestión Administrativa Agencia de Viaje Sol Viaje y Turismo de la ciudad de Babahoyo - Murillo Franco, Edinson Ramón (2021)
The current case study aims to carry out the computer application for the administrative management of the travel agency, sol travel and tourism of the city of Babahoyo, to identify the foundations of the problems that currently present, for this the qualitative research paradigm was used , the same one that approved us through an analysis to determine the characteristics of making the computer application for the administrative management of the travel agency, sol travel and tourism of the city of Babahoyo and thus aiming at solutions to the problems encountered, the type of Bibliographic research that helped us to the scientific foundation of the variables of the research topic.